Evidence jiných než vlastnických vztahů k nemovitostem - Stružka, Petr (2007)
The subject is recording of legal relations to real estate. In first part I put mind to history of registration of real estate and land registry. In second part is my concern on evidence of legal relations to real estate, especially to right of lien, right of user, right of refusal and way of evidence legal relations and fundamentals of recording of legal relatins to real estate.